Towards a Context Specific and Multidimensional Quality of Urban Life Model. Issue 1 (1st March 2019) - MacLean, Laura; Salama, Ashraf M.
Abstract : With the majority of people living in cities it has become increasingly important to examine the relationship between the qualities and characteristics of an urban setting and the perceived satisfaction of its users. Discourses on Quality of Urban life (QOUL) show that the preponderance of existing empirical studies and measurement frameworks have been developed based on Western case studies or standards. Rapid urbanisation of cities in Africa and Asia, however, has dramatically impacted the use of space, and in many cases has resulted in intense urban transformations that impacted communities. This prompts questions about the quality of life (QOL) of residents and the liveability of their environments. Thus, this research argues that although there are many aspects of urban life that are pan-cultural, there are also culture specific features that make urban life unique in each city or setting. Consequently, QOUL studies should balance universal values and context-specificities. Following identification and critique of QOUL models, the paper calls for a new model to examine context specificities. The model aims to highlight the important role that context and culture play in urban life while underscoring the relevant core dimensions of QOUL studies.